Modeling of operating history of the research nuclear reactor; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Naymushin A. G. Artem Georgievich; Chertkov Yu. B. Yuri Borisovich; Shchurovskaya M.; Anikin M. N. Mikhail Nikolaevich; Lebedev I. I. Ivan Igorevich (2016, 2016)
Title screen